TRADISI MESAMBAKAY PADA KOMUNITAS ADAT TOLAKI-MEKONGGA (Studi Etnografi di Kabupaten Kolaka) - diah, mohammad; Bahtiar, Bahtiar; Topo Jers, La Ode (Universitas Halu Oleo, 2021)
The research questions of this research are as follows: (1) How is the process of implementing mesambakay in Tolaki-Mekongga indigenous community in Kolaka Regency? (2) What is the symbolic meaning of mesambakay in the Tolaki-Mekongga customary community in Kolaka Regency? The objectives of this research are to: (1) know and explain the mesambakay process in Tolaki-Mekongga customary community in Kolaka Regency, (2) explain the symbolic meaning of mesambakay in the Tolaki-Mekongga customary community in Kolaka Regency. This research method uses ethnographic method with a qualitative approach as a research procedure that produces descriptive data in the form of written or oral explanations of people and observable behavior. The data analysis technique used in this study is in accordance with the statement expressed by Miles and Huberman (2009: 16-20) which states that data analysis activities in qualitative research consist of three stages carried out simultaneously, namely Data Reduction, Data Presentation and Conclusion. The results of this study indicate that: (1) The process of implementing the mesambakay ritual in the Tolaki-Mekongga customary community in Kolaka District shows a tradition that is continuously carried out by the people of Kolaka Regency, especially in Wundulako District. In practice, it turns out that the mesambakay ritual depicts a tradition of